A Novel Chinese Herbal and Corresponding Chemical Formula for Cancer Treatment by Targeting Tumor Maintenance, Progression, and Metastasis - Song, Ying-Chyi; Lee, Der-Yen; Yeh, Pei-Yen (Frontiers in Pharmacology, 2022)
We characterized a so-called "heirloom recipe" Chinese herbal formula (temporarily named Formula X) that contains five Chinese medical herbs, Huang-Lian (Coptis chinensis Franch. [Ranunculaceae]), Huang-Qin (Scutellaria baicalensis Georgi [Lamiaceae]), Bai-Wei (Vincetoxicum atratum (Bunge) C.Morren & Decne. [Apocynaceae]), E-Zhu (Curcuma aromatica Salisb. [Zingiberaceae]) and Bai-Zhu (Atractylodes macrocephala Koidz. [Asteraceae]). Formula X inhibited the growth of various cancer cells and decreased the expression levels of a panel of proteins, including CD133, Myc, PD-L1, and Slug, in cancer cells. We further found that the inhibition of growth and protein expression were exerted by Huang-Lian, Huang-Qin, and Bai-Wei (formula HHB), which exhibited the same biological effects as those of Formula X. Furthermore, we selected three active chemicals, berberine, baicalin, and saponin from Huang-Lian, Huang-Qin, and Bai-Wei, respectively, to produce a chemical formulation (formula BBS), which exhibited similar effects on cell growth and protein expression as those induced by formula HHB. Both the formulae HHB and BBS suppressed tumor growth in an animal study. Moreover, they decreased the protein levels of Myc and PD-L1 in tumor cells in vivo. In summary, we established a novel Chinese herbal formula and a chemical formula that targeted three important processes, tumor maintenance (tumor stem cells), progression, and metastasis, and that influenced the response of tumors to host immunosuppression, for the potentially effective treatment of cancer patients.